2019
DOI: 10.48550/arxiv.1908.04198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On simplified NP-complete variants of Not-All-Equal 3-Sat and 3-Sat

Andreas Darmann,
Janosch Döcker

Abstract: We consider simplified, monotone versions of Not-All-Equal 3-Sat and 3-Sat, variants of the famous Satisfiability Problem where each clause is made up of exactly three distinct literals. We show that Not-All-Equal 3-Sat remains NP-complete even if (1) each variable appears exactly four times, (2) there are no negations in the formula, and (3) the formula is linear, i.e., each pair of distinct clauses shares at most one variable.Concerning 3-Sat we prove several hardness results for monotone formulas with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Recently, Darmann and Döcker [6,Cor. 2] showed that for each fixed k ≥ 3 Monotone 3-Sat is NP-complete if each variable appears exactly k times unnegated und exactly k times negated.…”
Section: Clausesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Darmann and Döcker [6,Cor. 2] showed that for each fixed k ≥ 3 Monotone 3-Sat is NP-complete if each variable appears exactly k times unnegated und exactly k times negated.…”
Section: Clausesmentioning
confidence: 99%
“…In one instance, we reduce from Monotone 3-Sat*-(2, 2) [6] which is the variant of Monotone 3-Sat-(2, 2) where variables may appear more than once in a clause. Note that we can assume that each variable appears at most twice in a given clause, since each clause is monotone and there are only two unnegated and two negated appearances of any variable.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…We can obtain the following results by means of a reduction from the NAE-3-SAT problem. We now present the NAE-3-SAT problem, which is NP -complete; see [10,5].…”
Section: Introductionmentioning
confidence: 99%